Career Booster or Dead End? Entrepreneurial Failure and Its Consequences for Subsequent Corporate Careers - Verena Rieger; Jana Wilken; Andreas Engelen (Journal of Management Studies, 2022)
Human capital theory establishes that the human capital gained in prior work experience, such as in traditional corporations, is associated with subsequent entrepreneurial success. However, this perspective does not accommodate increasingly boundaryless careers, during which individuals switch between career tracks in both directions. As a result, research to date is unable to explain whether experience with entrepreneurial failure drives corporate career success. We extend existing human capital research by theorizing that and testing empirically whether entrepreneurial activity builds human capital that is conducive to a subsequent corporate career, even when the new venture fails. We provide two main studies, a résumé experiment with 80 recruiters and a study with a matched sample of 326 failed entrepreneurs and comparable graduates who started a career in a corporation, that support this notion. We find that failed entrepreneurs can have a corporate career advantage over those graduates who started a career in a corporation.
Keywords: 650; entrepreneurial experience; failure; human capital theory; personal initiative